2019
DOI: 10.1029/2019sw002278
|View full text |Cite
|
Sign up to set email alerts
|

A 21st Century View of the March 1989 Magnetic Storm

Abstract: On 13 March 1989, the largest magnetic storm of the last century caused widespread effects on power systems including a blackout of the Hydro-Québec system. Since then this event has become the archetypal disturbance for examining the geomagnetic hazard to power systems. However, even 30 years on from 1989, the story of exactly what happened in March 1989 is far from complete. This paper reexamines the information available about the March 1989 event and uses this to construct a timeline and description of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 49 publications
2
139
0
Order By: Relevance
“…With respect to the aurorae of these events, Hayakawa, Ebihara, Cliver, et al (2019) estimated, based on contemporary observations, that their equatorward extent reached ∼ 32 • MLAT during the 1909 superstorm, as opposed to 40 • MLAT estimated from particle precipitation measurements by satellites during the 1989 superstorm (Pulkkinen et al, 2012;Rich & Denig, 1992). Intense GICs occurred during both events, with several reports of geophysical disturbances on telegraph systems in 1909 (Hapgood, 2019;Hayakawa, Ebihara, Cliver, et al, 2019;Love et al, 2019b;Silverman, 1995), and on power transmission lines in 1989, particularly the power blackout in Québec, Canada (Allen et al, 1989;Boteler, 2019;Kappenman, 2006;Oliveira & Ngwira, 2017). During the 1989 event, the only event with satellite-based data amongst the four superstorms, the number of space objects "lost" in LEO increased dramatically around periods of maximum intensity due to errors introduced by storm heating effects into tracking systems (Allen et al, 1989;Burke, 2018;Joselyn, 1990).…”
Section: The Selected Magnetic Superstormsmentioning
confidence: 99%
“…With respect to the aurorae of these events, Hayakawa, Ebihara, Cliver, et al (2019) estimated, based on contemporary observations, that their equatorward extent reached ∼ 32 • MLAT during the 1909 superstorm, as opposed to 40 • MLAT estimated from particle precipitation measurements by satellites during the 1989 superstorm (Pulkkinen et al, 2012;Rich & Denig, 1992). Intense GICs occurred during both events, with several reports of geophysical disturbances on telegraph systems in 1909 (Hapgood, 2019;Hayakawa, Ebihara, Cliver, et al, 2019;Love et al, 2019b;Silverman, 1995), and on power transmission lines in 1989, particularly the power blackout in Québec, Canada (Allen et al, 1989;Boteler, 2019;Kappenman, 2006;Oliveira & Ngwira, 2017). During the 1989 event, the only event with satellite-based data amongst the four superstorms, the number of space objects "lost" in LEO increased dramatically around periods of maximum intensity due to errors introduced by storm heating effects into tracking systems (Allen et al, 1989;Burke, 2018;Joselyn, 1990).…”
Section: The Selected Magnetic Superstormsmentioning
confidence: 99%
“…Lakhina and Tsurutani () studied the 1989 event using SYM‐H data and Boteler () more recently studied it using ground magnetograms. Both analyses concluded that this was indeed an ICME‐ICME “compound event” with 2 MCs (and 2 sheaths) involved in causing the superstorm main phase.…”
Section: Addendummentioning
confidence: 99%
“…It is generally understood that midlatitude aurorae appear with great magnetic storms (e.g., Cid et al, 2014Cid et al, , 2015Daglis et al, 1999;Saiz et al, 2016;Schlegel & Schlegel, 2011;Vallance Jones, 1992), resulted from interplanetary coronal mass ejections (ICMEs) or shock with corotating interaction region, with the southward interplanetary magnetic field (Borovsky & Denton, 2006;Gonzalez et al, 1994;Richardson et al, 2006). This was especially the case with the extreme storms such as the Hydro-Québec storm in March 1989, where sequence of ICMEs cause one of the most extreme geomagnetic storms in the space age and significant extension of the auroral oval (Allen et al, 1989;Boteler, 2019;Cid et al, 2014;Yokoyama et al, 1998). As such, midlatitude auroral reports have formed one of the important clues to understanding the space weather and space climate in the past (e.g., Domínguez-Castro et al, 2016;Hayakawa, Mitsuma, et al, 2019;Lockwood et al, 2016;Lockwood & Barnard, 2015;Riley et al, 2018;Silverman, 1992;Usoskin et al, 2013Usoskin et al, , 2015Vaquero et al, 2010;Vázquez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%